Erosive Wear of Structured Carbon-Fibre-Reinforced Textile Polymer Composites under Sands Blasting - Tong Deng; Vivek Garg; Michael S.A. Bradley (Lubricants, 2024)
Textile polymer composite is made of structured fibre matrix using textile technologies in fabrication, and gains benefits from strong mechanical properties with extra light weight. However, erosion behaviours and associated wear mechanisms of the composites may be influenced by the fibre structures due to heterogeneous composition and complex architectural topologies. Understanding the erosive mechanisms of the structured composites can be important, not only for preventing surface damage and loss of mechanical strength but also for improving design and fabrication of the composites. This paper presents an experimental study of erosive wear under sand blasting on 3D woven carbon-fibre-reinforced textile composites with epoxy. The architectural topology methods of the composites include non-crimped bidirectional, tufted bidirectional, 3D layer-to-layer and 3D orthogonal textile methods. The erosion tests were conducted on four impact angles (20°, 30°, 45° and 90°) under one impact velocity at 40 m/s. The study results show that the erosive mechanism of the textile composites is different from that of the neat substrate material. The observations from this study also reveal the different erosive behaviours between the composites with different fibre structures. It concludes that architectural structures can influence the erosion of a textile composite but will not result in significant differences in the wear resistance of the composites (<20%).